The religion of the Etruscans - Bonfante, Larissa; Colonna, Giovanni; Edlund-Berry, Ingrid E. M.; De Grummond, Nancy Thomson; Krauskopf, Ingrid; Simon, Erika; Simon, Erika; Tatum, W. Jeffrey; Turfa, Jean MacIntosh; De Grummond, Nancy Thomson (University of Texas Press, 2021)
Frontmatter -- CONTENTS -- Editors’ Note -- List of Abbreviations -- Contributors to This Volume -- Preface -- I. Introduction: The History of the Study of Etruscan Religion -- II. Etruscan Inscriptions and Etruscan Religion -- III. Prophets and Priests -- IV. Gods in Harmony: The Etruscan Pantheon -- V. The Grave and Beyond in Etruscan Religion -- VI. Votive Offerings in Etruscan Religion -- VII. Ritual Space and Boundaries in Etruscan Religion -- VIII. Sacred Architecture and the Religion of the Etruscans -- Glossary -- Appendix A: The Etruscan Brontoscopic Calendar -- Appendix B: Selected Latin and Greek Literary Sources on Etruscan Religion -- Index